PENGARUH IKLIM KERJA TERHADAP KINERJA GURU PADA MADRASAH ALIYAH DI KECAMATAN GANTARANG KABUPATEN BULUKUMBA - Hamsah, Hamsah; Syamsudduha, ST.; Rahman, Ulfiani (Idaarah: Jurnal Manajemen Pendidikan, 2019)
This study aims to: 1) find out the description of the work climate at Madrasah Aliyah in Gantarang District, Bulukumba Regency; 2) find out the reality of teachers’ performance at Madrasah Aliyah in Gantarang District, Bulukumba Regency; 3) determine the effect of the work climate on teachers’ performance at Madrasah Aliyah in Gantarang District, Bulukumba Regency. This type of research is an ex post facto research as part of quantitative research. Respondents in this study were 75 teachers taken as a whole at Madrasah Aliyah in Gantarang District, Bulukumba Regency. Data collection techniques used are the scale of work climate, the scale of teachers’ performance and documentation, while the data analysis technique used is descriptive and inferential statistical analysis with hypothesis testing using simple linear regression analysis. Indicators of work climate tested for their effect on teacher performance include: trust in subordinates; openness in communicating environmental conditions; leadership that helps and appreciates; joint problem solving; teacher autonomy; kinship; being indifferent; authoritarian leadership; and low employee morale. While the indicators tested on teacher performance include: planning of learning activities programs, implementing learning activities and evaluating / evaluating learning. The results of this study indicate that the work climate has a positive effect on teachers’ performance with a coefficient of determination of 0.382. Thus, the magnitude of the influence of the work climate on teacher performance in Madrasah Aliyah in Gantarang District, Bulukumba Regency is 38.2% and 61.8% is determined by other factors.